2011
DOI: 10.1159/000328648
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Preformed Collateral Vessels in the Human Heart without Coronary Artery Disease

Abstract: Background: Coronary collaterals protect myocardium jeopardized by coronary artery disease (CAD). Promotion of collateral circulation is desirable before myocardial damage occurs. Therefore, determinants of collateral preformation in patients without CAD should be elucidated. Methods: In 106 patients undergoing coronary angiography who were free of coronary stenoses, a total of 39 clinical test variables were collected. The coronary collateral flow index (CFI) was measured. Stepwise multiple linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
41
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 67 publications
2
41
1
1
Order By: Relevance
“…A recent study showed that external counterpulsation which simulates physical exercise can induce collateral growth by increasing the shear force on the endothelium [9]. A lower heart rate may increase shear force on the endothelium due to the larger stroke volume and pulse pressure [10]. Individuals with a lower resting heart rate have a better developed collateral network [10], and regular physical exercise leads to a lower resting heart rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that external counterpulsation which simulates physical exercise can induce collateral growth by increasing the shear force on the endothelium [9]. A lower heart rate may increase shear force on the endothelium due to the larger stroke volume and pulse pressure [10]. Individuals with a lower resting heart rate have a better developed collateral network [10], and regular physical exercise leads to a lower resting heart rate.…”
mentioning
confidence: 99%
“…A lower heart rate may increase shear force on the endothelium due to the larger stroke volume and pulse pressure [10]. Individuals with a lower resting heart rate have a better developed collateral network [10], and regular physical exercise leads to a lower resting heart rate.…”
mentioning
confidence: 99%
“…
ABSTRACT
Aim: The aim of the present study is to investigate the prognostic value of Coronary Collateral Circulation (CCC) in patients with the first acute anterior wall ST Elevation Myocardial Infarction (STEMI) undergoing primary percutaneous coronary intervention w (p-PCI).
Material and Method: A total of 220 Patients with first acute 08, 95 %CI 1,07 to 1,26, p=0,03), Semptomların başlangıcın-dan p-PKG yapılıncaya kadar geçen süre ([OR] 1,6, 95 %CI 1,06 to 2,59, p=0,04),3, 95 %CI 1,04 to 10,9, p=0,04)
…”
mentioning
confidence: 99%
“…A previous large study of 450 patients with coronary artery disease that considered patient history, cardiovascular risk factors, medication use and angiographic data showed that the only independent determinant of adequate collateral circulation was the degree of coronary artery stenosis (8). In patients without coronary artery disease, the baseline heart rate has been described as the main predictor of collateralization (9). There is also evidence that genetic factors play a role (10).…”
mentioning
confidence: 99%